Foundations of multidimensional and metric data structures - Samet, Hanan (Amsterdam : Elsevier / Morgan Kaufmann, 2006)
With applications in computer graphics and visualisation, databases, geographic information systems (GIS) and spatial databases, game programming, image processing and computer vision, pattern recognition,solid modelling and computational geometry, similar retrieval and multimedia databases, VLSI design, and search aspects of bioinformatics
Περιέχει βιβλιογραφία και ευρετήριο
Keywords: Data structures (Computer science).; Computer algorithms